(untitled) (Ágora de Heterodoxias, 2015)
Dams play a very important role in current water supply systems since many years ago. These structures involve huge retained volumes of water and sediments, whereby total or partial failure may lead to enormous material damage and/or human losses. Using numerical software during project stage for modeling failure scenarios such as dam breaching represents a powerful tool for risk assessment as they are capable to estimate the consequences of any eventual flooding due to dam failure. Hereby it is presented the results of two (2) two-dimensional overtopping dam breaching study cases located in Lara state, Venezuela which have been modeled with ISIS 2D and Delft3D respectively, by using different methods and resources on a theoretical and practical experiences basis, highlighting water behavior as flooding wave propagates downstream. As a conclusion of an exhaustive analysis, it is possible to asseverate about the feasibility of using the procedures and software previously described for dam breach modeling from the consistency of the obtained values and the model stability, standing out as a gateway to the key field of dam break hydrodynamic modeling which is an area that has been poorly explored in Latin-America.